Historical blocking: CN 2019-06-08 (China) - Voidly (Voidly Global Censorship Index, 2019)
CRITICAL severity censorship detected in China. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2019-0007. Severity: critical. Confidence: 82%